Cross-cultural adaptation of the Parental Perceptions of Children’s Exposure to Tobacco Smoke instrument to the Brazilian context - Maria Alice Santos Tavares; Vicki Myers; Leandro Alberto Calazans Nogueira; Agnaldo José Lopes (BMC Research Notes, 2023)
Abstract Objective To perform a cross-cultural adaptation of the Parental Perceptions of Children’s Exposure to Tobacco Smoke (PPE) instrument to the Brazilian context. Results The cross-cultural adaptation process was performed in 10 stages. Four translators, eight specialists, and 35 primary care users participated in the study. Both translations were similar. The synthesis version that was back-translated was equivalent to the original. The committee of experts scored all items in the content validity index as 3 or 4, suggesting only small changes such as changing “photo” to “image” and “service balcony” to “service area”. After the completion of the first sequence of pretests, some adjustments were required by the committee of experts for the second round. The form of application of the self-administered questionnaire for the interview was changed, the Likert scale was reduced from 7 to 5 points, and the option “I don’t know” was added to questions 18, 19, and 20. After these adjustments, the instrument was well accepted by the study population and presented good internal consistency (Cronbach’s α score = 0.82). The PPE instrument, which assesses the perception of parents about their children’s exposure to cigarette smoke, was satisfactorily translated and adapted to the Brazilian context.